Identity: A Chamber of Torture - Castelli, Alberto (Verbum – Analecta Neolatina, 2024)
What emerges from the Twentieth-century is the relativity of external reality paralleled by the decomposition of the self. Identity is an unstable and nebulous concept that social constructionist theories have transformed into a series of external embodiments, hence reducing it to a myth. But when self-constituting ties are severed, identity begins to unravel. With Luigi Pirandello’s and Franz Kafka’s narrative, the self must be confirmed by the judgment of the Other. In the dynamic relationship between the “I” and the Other, Pirandello chooses the former, and Kafka the latter. With Pirandello, the individual becomes a madman, but with Kafka, the choice of the Other transforms the individual into a monster.